Gut microbiota composition in patients with advanced malignancies experiencing immune-related adverse events - Liu, Xinyu; Tang, Hao; Zhou, Qingyang; Zeng, Yanlin; Lu, Bo; Chen, Dan; Li, Yue; Qian, Jiaming; Chen, Minjiang; Zhao, Jing; Xu, Yan; Wang, Mengzhao; et al. (Frontiers in Immunology, 2023)
The gut microbiota is implicated in the occurrence and severity of immune-related adverse events (irAEs), but its potential as a biomarker of irAEs has yet to be established. From May 2020 to August 2021, 93 fecal samples were prospectively collected from 37 patients with advanced thoracic cancers treated with anti-PD-1 therapy, and 61 samples were collected from 33 patients with various cancers developing different irAEs. 16S rDNA amplicon sequencing was performed. Antibiotic-treated mice underwent fecal microbiota transplantation (FMT) with samples from patients with and without colitic irAEs. Microbiota composition was significantly different in patients with and without irAEs (P=0.001) and with and without colitic-type irAEs (P=0.003). Bifidobacterium, Faecalibacterium, and Agathobacter were less abundant and Erysipelatoclostridium more abundant in irAE patients, while Bacteroides and Bifidobacterium were less abundant and Enterococcus more abundant in colitis-type irAE patients. Major butyrate-producing bacteria were also less abundant in patients with irAEs than those without (P=0.007) and in colitic vs. non-colitic irAE patients (P=0.018). An irAE prediction model had an AUC of 86.4% in training and 91.7% in testing. Immune-related colitis was more common in colitic-irAE-FMT (3/9) than non-irAE-FMT mice (0/9). The gut microbiota is important in dictating irAE occurrence and type, especially for immune-related colitis, possibly by modulating metabolic pathways.